The relationship between gallstone disease and the genetic variants of the sterol transporter adenosine triphosphate–binding cassette G8 and G5 in Egyptians - Menna A. Hassan; Salwa M. Abo El-Khair; Noha M. Mesbah; Dina M. Abo-Elmatty; Asmaa R. Abdel-Hamed (Egyptian Journal of Medical Human Genetics)
Abstract Background Gallstones are abnormal lumps in the gallbladder or biliary tract due impaired cholesterol, bilirubin, or bile salt metabolism. The Adenosine triphosphate binding cassette transporter genes G5 and G8 (ABCG5, ABCG8) are two half transporters which work together as a heterodimer to regulate cholesterol levels in bile, and any alterations in their function can contribute to gallstone formation. The primary objective of this study was to evaluate the association between three specific polymorphisms—ABCG5 i7892T > C, ABCG5 Q604E, and ABCG8 D19H—and the risk of gallstone disease (GSD) in Egyptian females. These polymorphisms result from nucleotide substitutions in the gene sequences, which affect the transporter’s ability to efficiently regulate cholesterol secretion into the bile. This alteration can lead to cholesterol supersaturation in the bile, a key factor in the development of cholesterol gallstones. Additionally, the study aimed to examine the impact of these genetic variations on serum lipid profile to understand their role in modulating biochemical markers associated with GSD. Furthermore, the study sought to investigate haplotype patterns and explore their combined effects on disease susceptibility, providing deeper insight into the genetic factors that contribute to the development of GSD. Methods The study included 100 female patients diagnosed with gallstones and 100 healthy controls. Genotyping of single nucleotide polymorphisms (SNPs) was performed using allelic discrimination pre-designed TaqMan polymerase chain reaction method. Various laboratory investigations were measured using enzymatic colorimetric methods, and hematology analyzer was used for the whole blood count test. Results Between patients with gallstone disease and healthy controls, there were statistically significant differences in the distribution of these genes polymorphisms. Q604E CC genotype (OR = 15.2; P = 0.004) and C allele (OR = 2; P = 0.007) in ABCG5 (rs6720173) as well as D19H GC genotype (OR = 2.9; P = 0.002) and C allele (OR = 2; P = 0.004) in ABCG8 (rs11887534) were significantly more frequent in gallstone patients. The CCC haplotype is a statistically significant predictor of GSD. Conclusions This study suggests that ABCG8 D19H (G/C) and ABCG5 Q604E (C/C) genotypes may play a significant role in GSD susceptibility among Egyptian females. Graphical abstract